Ethical Dilemmas in Neonatal Care at the Limit of Viability - Lilijana Kornhauser Cerar; Miha Lucovnik (MDPI AG, 2023)
Advances in neonatal care have pushed the limit of viability to incrementally lower gestations over the last decades. However, surviving extremely premature neonates are prone to long-term neurodevelopmental handicaps. This makes ethics a crucial dimension of periviable birth management. At 22 weeks, survival ranges from 1 to 15%, and profound disabilities in survivors are common. Consequently, there is no beneficence-based obligation to offer any aggressive perinatal management. At 23 weeks, survival ranges from 8 to 54%, and survival without severe handicap ranges from 7 to 23%. If fetal indication for cesarean delivery appears, the procedure may be offered when neonatal resuscitation is planned. At a gestational age ≥24 weeks, up to 51% neonates are expected to survive the neonatal period. Survival without profound neurologic disability ranges from 12 to 38%. Beneficence-based obligation to intervene is reasonable at these gestations. Nevertheless, autonomy of parents should also be respected, and parental consent should be sought prior to any intervention. Optimal counselling of parents involves harmonized cooperation of obstetric and neonatal care providers. Every fetus/neonate and every pregnant woman are different and have the right to be considered individually when treatment decisions are being made.